'All dwarfs are bastards': Game of Thrones as disability studies pedagogy. (1st March 2019) - Cook, Tanya N.
This article explores how Game of Thrones can be used as a pedagogical tool to understand the social model of disability and its essential claim that it is society that disables individuals. Through analysis of main character, Tyrion Lannister, this article works to frame an understanding of disability as socially constructed identity and reveal how the concept of a 'normal' body is also a social construction. This article also explores the pedagogical implications of dwarfism as a stigmatized identity in Game of Thrones. Not only can this analysis be used as teaching exemplar to help further understanding of the social model of disability, it can challenge instructors to rethink the ways in which their pedagogy creates a classroom experience that alternately enables or disables.